Effect of sesamol on damaged peripheral nerves: Evaluation of functional, histological, molecular, and oxidative stress parameters - Nastaran Amerian; Athar Talebi; Manouchehr Safari; Hamid Reza Sameni; Ali Ghanbari; Parisa Hayat; Moslem Mohammadi; Maryam Ardekanian; Sam Zarbakhsh (Mashhad University of Medical Sciences, 2022)
Objective: Peripheral nerve injury is a clinical problem that may cause sensory and motor inabilities. Sesamol is an antioxidant that can help in repairing damaged central nervous system (CNS) and other organs. The present study aimed to investigate whether the antioxidant effects of sesamol could improve the function, structure, and myelination in rats' damaged peripheral nervous system (PNS).Materials and Methods: In this study, 28 adult male Wistar rats were randomly divided into four groups. In the sham group, the sciatic nerve was exposed and restored to its place without inducing crush injury. The control received DMSO (solvent) and the two experimental groups received 50 or 100 mg/kg sesamol intraperitoneally for 28 days after sciatic nerve crush injury, respectively. Next, sciatic function index (SFI), superoxide dismutase (SOD) activity, malondialdehyde (MDA) level, expression of nerve growth factor (NGF) and myelin protein zero (MPZ) proteins in the sciatic nerve, and histological indices of the sciatic nerve and gastrocnemius muscle were evaluated. Results: The results showed that sesamol reduced oxidative stress parameters, increased expression of NGF and MPZ proteins, and improved function and regeneration of the damaged sciatic nerve. Furthermore, a significant regeneration was observed in the gastrocnemius muscle after treatment with sesamol. Although administration of both doses of sesamol was useful, the 100 mg/kg dose was more effective than the 50 mg/kg one.Conclusion: The results suggest that sesamol may be effective in improving damaged peripheral nerves in rats by reducing oxidative stress and increasing the expression of NGF and MPZ proteins.